2000
DOI: 10.3314/jjmm.41.161
|View full text |Cite
|
Sign up to set email alerts
|

Cells of Different Ploidy Are Often Present Together in Cryptococcus neoformans Strains.

Abstract: We examined the ploidy of C. neoformans strains using both laser scanning cytometry and a transfers. Thus, a cellular ploidy shift was shown to occur widely in C. neoformans strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, one should take into account that our analysis of genome size and ploidy was based on the uninucleated cell subpopulation presenting the lowest DNA content (R 1 ), within a total population of 30,000 cells. In this sense, it is not possible to discard the presence of a small number of cells with distinct ploidy levels within the total cell population, a phenomenon that has already been reported for the pathogenic fungus Cryptococcus neoformans (Hata et al, 2000). This study provides information that addresses fundamental questions of P. brasiliensis biology, namely genome size and ploidy, an important asset for the development/ design of molecular techniques (e.g., gene disruption and/or over-expression) and the future genetic manipulation of this human dimorphic pathogen.…”
Section: Discussionmentioning
confidence: 92%
“…However, one should take into account that our analysis of genome size and ploidy was based on the uninucleated cell subpopulation presenting the lowest DNA content (R 1 ), within a total population of 30,000 cells. In this sense, it is not possible to discard the presence of a small number of cells with distinct ploidy levels within the total cell population, a phenomenon that has already been reported for the pathogenic fungus Cryptococcus neoformans (Hata et al, 2000). This study provides information that addresses fundamental questions of P. brasiliensis biology, namely genome size and ploidy, an important asset for the development/ design of molecular techniques (e.g., gene disruption and/or over-expression) and the future genetic manipulation of this human dimorphic pathogen.…”
Section: Discussionmentioning
confidence: 92%
“…As to its timing, there are three logical possibilities, i.e., at "Start" concomitantly with DNA synthesis as in the case of S. cerevisiae (Lew 1997), concomitantly with initiation of budding under the control of the B-factor, or concomitantly with the actual onset of mitosis as in Schizosaccharomyces pombe (Ding et al 1997). It is relevant that C. neoformans cells exhibit a high probability of spontaneous diploidization (Hata et al 2000), which is explained naturally if spindle pole body duplication is committed together with DNA synthesis at "Start" as follows. Execution of the B-factor is easily prolonged under several conditions until the G 2 phase, i.e., budding does not occur even after completion of DNA synthesis (legend to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These cells should be in the earliest morphologically discernible cell cycle point. DNA content of these cells was standardized as = 1. c Single colony isolated before use, as described in [10]. Where single-cell isolation was not done, only cells having similar sizes were measured to avoid possible errors due to involvement of di¡erent ploidy (see [10] for detail).…”
Section: Resultsmentioning
confidence: 99%
“…This independence between DNA synthesis and budding enables cells to continue to grow even after the cell population stops dividing, producing large unbudded G 2 cells in the stationary phase [4], in contrast to the smaller cells in S. cerevisiae [9]. Recently we reported that ploidy shift occurs frequently in C. neoformans [10]. This may be attributed to a relaxed coordination of DNA synthesis and budding; ploidy shift may result if a cell that has completed DNA synthesis remains unbudded for some period, and then starts a new cell cycle (DNA synthesis) without completing the previous cell division cycle.…”
Section: Discussionmentioning
confidence: 99%